THE INFLUENCE OF COLONIALISM ON THE COASTAL COMMUNITIES IN PARIAMAN THROUGH ADILLA'S NAKHODA PESISIR BARAT - Dahlia Ramadhani; Mikail A. F. Djauhari Amrin; Nur Grace; Serli Aulia; Roys A. Saputra; Mutmainnah Mutmainnah (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2025)
This research aims to examine the impact of colonialism's influence on the lives of the coastal society of Pariaman, West Sumatra, focusing on cultural, social and economic interactions. The research's foundation is Ivan Adilla's short novel Nakhoda Pesisir Barat, which recounts the late 19th-century life of a merchant named Muhammad Saleh under Dutch colonial rule. Examining how colonialism affected trade, education, and local identity, this research used a qualitative methodology with a historical perspective and narrative analysis, drawing on the theories of Frantz Fanon and Immanuel Wallerstein. The results of the research show that colonialism brought changes to education and economic dynamics, particularly in international trade and social significantly. However, colonial dominance also produced subordinate systems that had an impact on the psychology and identity of the coastal inhabitants of Pariaman.